ST-Elevated Myocardial Infarction Presented with Giant Coronary Artery Ectasia - Dhamodaran , K.; Kasha , Abhishek (New Advances in Medicine and Medical Science Vol. 7, 2023)
The present case study highlights about giant coronary artery ectasia presenting with ST elevation myocardial infarction. “Coronary artery ectasia (CAE) is an aneurysmic abnormality of the artery characterized by diffuse dilatation, with a luminal diameter 1.5× wider than that of adjacent normal segments. A 56-year-old diabetic who does not smoke came in with chest pain that had lasted more than twelve hours. He was hemodynamically stable during the examination, and the cardiac auscultation was unremarkable.Repeat ECG after loading with DAPT and heparin showed ST-segment resolution, which was consistent with sinus rhythm and suggestive of anteroseptal myocardial infarction. An echocardiogram revealed hypokinesia of the anterior walls at the apex and the anteroseptal region, with a 56% LV ejection fraction. Coronary angiogram revealed Non-obstructive giant ectatic coronaries with slow contrast clearance, patient had an episode of ventricular tachycardia during a coronary angiogram, DC cardioverted. The patient was initially on parenteral LMWH and DAPT. He was discharged with antiplatelet (Aspirin 75 mg once a day) and anticoagulants (Rivaroxaban 2.5 mg 12th hourly), beta-blocker. Cardiac CT revealed Mild coronary artery disease with a calcium score – 30, and no significant coronary artery stenosis. Diffusely ectatic coronary arteries. “Initial studies have recommended the use of long-term oral anticoagulation on the premise of an increased risk of thrombosis in ectatic segments.